Paediatric and Adolescent civilian gunshot injuries: a 10 year epidemiological study - Verfuss, Frances (Division of General Surgery, 2025)
Introduction: In South Africa, the prevalence of violent crime, especially involving firearms, poses a significant public health challenge, particularly when it affects children. Previous studies showed a decrease in paediatric civilian gunshot injuries following the introduction of the 2004 Firearms Control Act. This study examines the epidemiological trends of gunshot injuries in children from January 2011 to December 2020. Methods: A descriptive cross-sectional study was performed on children aged 0-12 years presenting to the Red Cross War Memorial Children's Hospital (RXH) in Cape Town with gunshot injuries from January 2011 to December 2020. The data were drawn from the ChildSafe database and hospital records. We evaluated demographics, injury specifics, and orthopaedic outcomes. Results: The number of gunshot wounds(GSW) in the observational record showed an increasing trend of +2.69 (95%CI 1.05 – 4.33) patients per year with a total of 236 patients affected. There was a male predominance (56.8%), with the largest age group affected being children aged 5-9 years (44%). Orthopaedic injuries were prevalent in 69 patients (29.2%), including fractures and injuries to the peripheral nerves and spinal cord. A total of 71 fractures were recorded, with 54 occurring in the extremities and 17 involving the spine or pelvis. The lower extremities were most affected, necessitating surgical interventions such as external fixators and/or femur nails. Peripheral nerve injuries and spinal cord injuries resulted in significant long-term morbidities. The severity and complexity of all assessed injuries often required multiple surgical procedures and extended hospital stays, with an admission length of ~10 days, with some patients requiring intensive care (17.37% of cases). Morbidity included complications like wound infections and long-term disabilities such as paralysis and traumatic brain injuries. Conclusion: Despite legislative measures aimed at reducing such incidents, this study reveals an upward trend in gunshot injuries among children in Cape Town. Gunshot injuries remain a significant and increasing public health challenge among paediatric populations in Cape Town, with profound implications for morbidity, mortality, and healthcare resource utilization. Addressing this issue requires a comprehensive and multi-sectoral approach that prioritizes prevention, early intervention, and addressing the underlying social determinants of violence.